Ceaseless interruptions: the tear of the form in Cent mille milliards de poèmes, by Raymond Queneau, Tom, Tom, the Piper’s son, by Ken Jacobs, and Patterns, by Gerhard Richter - Costa, Alexandre Rodrigues da (ARS, 2017)
Our study aims to analyze the formless, anti-concept formulated by Georges Bataille, applying it to works Cent mille milliards de poèmes, by Raymond Queneau, Tom, Tom, the Piper's son, by Ken Jacobs, and Patterns: divided, mirrored, repeated, by Gerhard Richter. These works are open through tears, to the inability to set limits, since they generate excesses of meanings, which are based on the instability of form.